2009
DOI: 10.1016/s0929-6646(09)60092-9
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Methods Used by Women in Korea, Sweden, Taiwan and the United States

Abstract: Different countries contrast greatly in the agents used in suicide by poisoning but not in patterns of violent methods used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
3
16
0
1
Order By: Relevance
“…In England and Wales, the most common methods of suicide were hanging (38.6%) and self-poisoning (25.9%; Hunt et al, 2010), and the results were comparable with previous studies including those conducted in Korea, Sweden, and the United States (Chen et al, 2009b). However, we have found in our study that there were 299 (76.3%) of 392 victims who used self-poisoning, which was more likely chosen by women and by those without mental disorders.…”
Section: Discussionsupporting
confidence: 86%
“…In England and Wales, the most common methods of suicide were hanging (38.6%) and self-poisoning (25.9%; Hunt et al, 2010), and the results were comparable with previous studies including those conducted in Korea, Sweden, and the United States (Chen et al, 2009b). However, we have found in our study that there were 299 (76.3%) of 392 victims who used self-poisoning, which was more likely chosen by women and by those without mental disorders.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, almost half of women from Korea and Taiwan used pesticides. 21 The present study revealed that the highest number of victims were in the fourth decade (36.09%). We think because it is the mean range for age of foreign laborers in KSA.…”
Section: Discussionsupporting
confidence: 46%
“…Studies agree that firearms and hanging are the most lethal suicide means (Card, 1974;Chen, Park, & Lu, 2009;Elnour & Harrison, 2008;Miller et al, 2004;Shenassa, Catlin, & Buka, 2003;Spicer & Miller, 2000;Spittal, Pirkis, Miller, & Studdert, 2012;Vyrostek, Annest, & Ryan, 2004). Other methods traditionally considered highly dangerous are poisoning with gases (Elnour & Harrison, 2008), jumping from heights (Abrams, Marzuk, Tardiff, & Leon, 2005), drowning (Miller et al, 2004) and motor vehicle exhaust (Spittal et al, 2012), while poisoning with drugs, pill overdose and other poisons are usually more common in suicide attempts than in complete suicide (Elnour & Harrison, 2008;Fox & Weissman, 1975;Miller et al, 2004;Spicer & Miller, 2000).…”
Section: Suicide Methodsmentioning
confidence: 99%
“…Other methods traditionally considered highly dangerous are poisoning with gases (Elnour & Harrison, 2008), jumping from heights (Abrams, Marzuk, Tardiff, & Leon, 2005), drowning (Miller et al, 2004) and motor vehicle exhaust (Spittal et al, 2012), while poisoning with drugs, pill overdose and other poisons are usually more common in suicide attempts than in complete suicide (Elnour & Harrison, 2008;Fox & Weissman, 1975;Miller et al, 2004;Spicer & Miller, 2000). With regard to gender differences, men usually use more lethal means than women (Cibis et al, 2009): in fact, men tend to use, above all, firearms (Cattell, 2000;Kaplan et al, 2009), while women most often employ self-poisoning (Cattell, 2000;Chen, Park, & Lu, 2009). In addition, elderly people tend to adopt more violent methods as impulsive and aggressive subjects (Dumais et al, 2005).…”
Section: Suicide Methodsmentioning
confidence: 99%